Receptor mechanisms of thymoquinone-induced hypotension in normotensive rats - Mizher, Hussam A.; Noor, Noriah Mohd; Azzubaidi, Marwan Saad (2014)
Nigella sativa (NS), more commonly known as ‘’Habbattu Sauda’’, is a plant that is traditionally used to control hypertension. Evidence based studies revealed that NS exerts diuretic and blood pressure lowering effect in spontaneously hypertensive rat. While the volatile oil of NS acts centrally by indirect and direct mechanisms to induce cardio-depressant effect in urethane-anaesthetized rats, Thymoquinone (TQ) represents the main active constituent in the volatile oil, which could be the principal substance of the direct mechanism. Objective was to evaluate the hypotensive effect of TQ and its dose-response relationship in normotensive adult rats using the non-invasive tail-cuff technique. To investigate TQ mechanism of action through muscarinic and β adrenergic receptors. Three doses of TQ (2.5, 5 and 10 mg\kg) were used for assessing TQ hypotensive effect in 3 groups of rats (n=5) under sodium pentobarbital anesthesia. TQ was administered intraperitoneally, and mean arterial blood pressure (MAP) was obtained from recording systolic and diastolic pressure readings using the non-invasive tail-cuff technique and the dose-response relationship was obtained. MAP was then measured for other 2 animal groups pretreated either with atropine (P-at) or propranolol (P-pro) followed by 10 mg/kg TQ. This study confirms the dose-related hypotensive effect of TQ. The study showed that the mechanism of TQ-induced hypotension involves at least stimulation of vascular muscarinic receptors, but not β-adrenergic receptors. This study provides an evidence for the traditional use of Nigella sativa for treatment of hypertension.